CRIPTO-1 Is Immunolocalized in the Syncytiotrophoblast of Ampullary Pregnancies. (8th April 2022) - Cabar, Fábio Roberto; Pereira, Pedro Paulo; Bandeira, Carla Letícia; Bevilacqua, Estela; Schultz, Regina; Francisco, Rossana Pulcineli Vieira
Abstract : Introduction . Controlling the invasive activity of trophoblastic tissue has not been elucidated. In the accreta placenta, the invasion of placental tissue is directly related to the expression of CRIPTO-1 at the maternal-fetal interface. The aim of this study is to evaluate if the expression of the CRIPTO-1 is related to different degrees of trophoblast invasion into the tube wall in ampullary pregnancy. Methods . Prospective study with 21 patients with ampullary tubal pregnancy undergoing salpingectomy. Anatomopathological evaluation determined the degree of invasion of trophoblast tissues into the tubal wall and grouped the samples into invasive degrees I, II, or III. The groups were compared for tissue expression of CRIPTO-1 using the Kruskal-Wallis nonparametric test. p values lower than 0.05 were considered significant. Results . Quantitative expression of CRIPTO-1 differed in each of the three groups of trophoblast invasion in the tubal wall in ampullary pregnancies (p < 0.001 ). There is a difference between groups when grade I + grade II versus grade III (p < 0.001 ) and grade I versus grade II + grade III (p < 0.001 ). The tissue expression of CRIPTO-1 in ectopic trophoblasts showed that deeper invasion of the tubal wall was associated with stronger expression than in shallow invasion (p < 0.001 ). Discussion . In ampullary pregnancies, the depth of penetration of trophoblast tissue in the tubal wall is related to CRIPTO-1 tissue expression.